A Conserved Glycoside Hydrolase Family 7 Cellobiohydrolase PsGH7a of Phytophthora sojae Is Required for Full Virulence on Soybean - Tan, Xinwei; Hu, Yuyao; Jia, Yuli; Hou, Xiaoyuan; Xu, Qian; Han, Chao; Wang, Qunqing (Frontiers in Microbiology, 2020)
Phytopathogens deploy glycoside hydrolases(GHs) to disintegrate plant cell walls for nutrition and invasion. However, the pathogenic mechanisms of the majority of GHs in virulence remain unknown, especially in oomycetes. In this study, a gene encodes a GH7 family cellobiohydrolase, named PsGH7a, was identified in Phytophthora sojae. PsGH7a was highly induced during the cyst germination and infection stages. PsGH7a is conserved in oomycetes, and shares a high amino acid sequence identity (>85%) within Phytophthora genus. The recombinant PsGH7a catalyzes the hydrolysis of β-1,4-glucan and avicel, which represent the major components of cellulose in plant cell wall. The mutation of catalytic residue Glu236 to alanine (Ala), resulting in severe loss of catalytic activity. In addition, the PsGH7a promotes Phytophthora invasion, while the mutant can not. Notably, PsGH7a protein triggers hypersensitive cell death in diverse plants. To investigate its biological function, we generated PsGH7a knockout mutants via the CRISPR/Cas9 system. Compared with the wild-type strain, the mutants showed reduced virulence in soybean, indicates PsGH7a is indispensable to P.sojae virulence.